Disasters: Core Concepts and Ethical Theories (Advancing Global Bioethics,, 2018)
This Open Access Book is the first to examine disasters from a multidisciplinary perspective. Justification of actions in the face of disasters requires recourse both to conceptual analysis and ethical traditions. Part 1 of the book contains chapters on how disasters are conceptualized in different academic disciplines relevant to disasters. Part 2 has chapters on how ethical issues that arise in relation to disasters can be addressed from a number of fundamental normative approaches in moral and political philosophy. This book sets the stage for more focused normative debates given that no one book can be completely comprehensive. Providing analysis of core concepts, and with real-world relevance, this book should be of interest to disaster scholars and researchers, those working in ethics and political philosophy, as well as policy makers, humanitarian actors and intergovernmental organizations.